2017
DOI: 10.1057/s41287-017-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Transition? Declining Returns to Education in Vietnam

Abstract: There is evidence of a rapid increase in the returns to education in Vietnam in the 1990s and 2000s. There was a substantial change in education policy in the 2000s, especially opening up education opportunities for education providers to expand educational facilities and training.These changes could lead to a decline in the returns to education. To provide up-to-date estimates of the returns, we re-visit the returns using updated large-scale survey data to 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 27 publications
6
21
0
3
Order By: Relevance
“…Keeping all other factors constant, Model 1 shows that on average, an additional year of schooling would raise per capita income by about 500,000 VND (23.80 USD). This result accords with recent findings in Vietnam (Doan, Le, & Tran, ; Tran ; Tran et al, ). Nevertheless, the estimates in Model 2 and Figure show that the effect tended to be greater for higher quantiles, suggesting that there turn on education is higher for better‐off households.…”
Section: Resultssupporting
confidence: 93%
“…Keeping all other factors constant, Model 1 shows that on average, an additional year of schooling would raise per capita income by about 500,000 VND (23.80 USD). This result accords with recent findings in Vietnam (Doan, Le, & Tran, ; Tran ; Tran et al, ). Nevertheless, the estimates in Model 2 and Figure show that the effect tended to be greater for higher quantiles, suggesting that there turn on education is higher for better‐off households.…”
Section: Resultssupporting
confidence: 93%
“…At this level of aggregation, there is no indication that the convergence and subsequent reversal of gender education gaps payed off for women in Viet Nam. This is consistent with estimates of the conditional gender earnings gap showing no signs of decreasing during the same period (Oostendorp and Doan 2013;Doan et al 2018). From the perspective of this paper, these results show no discernible link between gender differences in returns and enrolments.…”
Section: Introductionsupporting
confidence: 89%
“…Standard linear regression techniques (e.g., ordinary least squares or fixed/random effects estimators) have been commonly used for considering the effect of education on household income or wage income (e.g., Doan et al, 2018;Lekobane & Seleka, 2017;Psacharopoulos & Patrinos, 2004;Tran, 2015). This mean approach looks at the average relationship between education and economic welfare based on the conditional mean of the outcome distribution.…”
Section: Econometric Modelsmentioning
confidence: 99%
“…Over the last decades, Vietnam's focused investments in developing primary education, combined with greater access to all levels, have paid off, and have enabled an increasing proportion of the population to exploit the advantages of expanding economic opportunities (WB, 2015). Numerous studies have found positive effects from education, among other factors, on poverty reduction and household income (Cloutier, Cockburn, & Decaluwé, 2008;Nguyen, Phung, & Westbrook, 2015) and wage income (Doan, Le, & Tran, 2018).…”
Section: Introductionmentioning
confidence: 99%